Use of crosslinking agent to produce high‐performance PLA/EVA blends via reactive processing. Issue 1 (12th October 2022) - Ferreira, Eduardo da Silva Barbosa; Luna, Carlos Bruno Barreto; dos Santos Filho, Edson Antonio; Wellen, Renate Maria Ramos; Araújo, Edcleide Maria
Abstract: Poly (lactic acid) (PLA) is one of the most currently investigated polymers due to its production from renewable sources and biodegradability. Being a brittle polymer, PLA has low toughness, limiting its use for commercial applications. Therefore, the present work aims to produce PLA blends, using the ethylene‐vinyl acetate copolymer (EVA), dynamically vulcanized with dicumyl peroxide (DCP) as a crosslinking agent. A 70/30 mixture of PLA/EVA was produced with 0.2, 0.4, 0.6, 0.8, and 1.0 phr DCP. The produced blends were characterized by torque rheometry, melt flow index (MFI), gel content, thermogravimetry (TG), and differential scanning calorimetry (DSC). Tensile properties, impact strength, heat deflection temperature (HDT), and blends morphologies (SEM) were also studied. The presence of increased dynamically vulcanized systems with added DCP was verified through torque rheometry, MFI, and gel content. Substantial increases in the impact strength and elongation at break were observed in PLA/EVA/DCP, providing super‐tough materials at 0.6, 0.8, and 1.0 phr of DCP, with impact strengths of 829.5, 860.3, and 890.2 J/m and elongation at break of 138.5, 146.8, and 120.4%, respectively. These results are promising when compared with engineering polymers and blends. This is probably due to in situ compatibilizer PLA‐g‐EVA, which resulted in a homogeneous morphology as evidenced by SEM images. Abstract :